Finnish subject teachers’ beliefs and use of information and communication technology in Home Economics - Sundqvist, Karin; Korhonen, Johan; Eklund, Gunilla (Nordic journal of digital literacy, 2020)
The importance of using information and communication technology (ICT) is being increasingly highlighted in education and curriculum frameworks in European countries. However, little attention has been given to using ICT in relation to the school subject of Home Economics (HE). Thus, the aim of this study is to explore Finnish subject-teachers’ use of ICT in HE, specifically focusing on frequency, purpose of use, and teachers’ beliefs. The data was collected through an online questionnaire, and the sample comprises 161 subject-teachers in HE in grades 7–9. The results revealed three dimensions of ICT use among HE teachers. Further, the K-means cluster analysis identified three distinct ICT-user profiles among subject-teachers in HE: infrequent ICT users (n = 60), specific ICT users (n = 43), and frequent ICT users (n = 58). Infrequent ICT users are characterized by low ICT use and neutral beliefs regarding the use of ICT in HE. Specific ICT users mainly focus on using ICT for administration and lesson planning and hold negative beliefs regarding the use of ICT. Frequent ICT users are the most common and positive ICT users and are also most confident about using ICT in HE. This study aims to provide a better understanding of subject-teachers’ use of ICT in HE in lower secondary education in Finland. The results suggest a relationship between teachers’ beliefs and purpose of use in terms of facilitating pupils’ learning. When identifying the three ICT user profiles, it became even more evident that the use of ICT for learning purposes was rather infrequent among HE teachers. In order to enhance teaching in HE, subject-teachers should be supported to use ICT for instructional purposes in a manner that will benefit pupils’ learning.